Effect of pre-sowing seed treatments on seed quality parameters of durum wheat (Triticum durum Desf.) under laboratory conditions - Nisha Ramani; Patil, Kalyanrao; Pandya, Mihir (Journal of Cereal Research, 2024)
An experiment was conducted during 2023-24 to study the effect of pre-sowing seed treatments on quality parameters of durum wheat seeds under laboratory conditions. The laboratory experiment was designed in Factorial CRD with wheat varieties viz., GW 1, GW 1346 and GADW 3. The given priming and with, T2: KNO3 (1%), T3: Salicylic Acid (100 ppm), T4: CaCl2 (250 ppm) and T5: H2O2 (100 mM). T6: Sodium Lauryl Sulphate, T7: Calcium Peroxide, T8: Bacillus subtilis and T9: Bio NPK. T1 was taken as control. The research results pertaining to the seed quality parameters as influenced by different pre-sowing seed treatments, wheat varieties and their interaction recorded significant variations. Among pre-sowing treatments priming with KNO3 @ 1% (T2) recorded significantly highest germination (88.56 %), seedling root length (6.68 cm), seedling shoot length (5.62 cm), seedling length (12.30 cm), seedling fresh weight (1.24 g), seedling dry weight (0.151g), seedling vigour index I (1093.60) and seedling vigour index II (13.49) based on analysis. Lowest germination per cent and other seed quality characters were recorded by Salicylic Acid priming (T3) and unprimed seeds (T1). Significantly highest germination (89.37 %), seedling root length(6.28 cm), seedling shoot length (5.32 cm), seedling length (11.6 cm), seedling fresh weight(0.98 g), seedling dry weight (0.149 g), seedling vigour index I (1040.24) and seedling vigour index II (13.40) were recorded by durum wheat variety GW 1.